Rancang Bangun Aplikasi Simpan Pinjam pada Koperasi Sumber Rejeki Surabaya - Finna Puspitasari; Haryanto Tanuwijaya; Vivine Nurcahyawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Koperasi Sumber Rejeki Surabaya is the type of Credit Unions which aims to provide storage services and loan capital for the community and surrounding surabaya area. All this time transaction in Koperasi Sumber Rejeki Surabaya done manually. With these processes have a problems such as piling files, recording the activity of deposit and loan transactions to be slow and spend a lot of time and susceptible to errors in preparing reports. Therefore we need tools that can simplify the process of savings and loans. With these problems Koperasi Sumber Rejeki Surabaya wanted to create an application that can backup deposit and loan transaction documents, storing data and displays all deposit and loan transaction documents, assist employees in managing deposits and loans well and useful for its users. Applications savings and credit cooperatives can improve employee performance so that they can save time and speed up the work. With the application of savings and loan is expected all problems can be overcome and cooperatives can improve the performance of cooperative employees so as to save time and speed up the work.